PERAN APARAT KEPOLISIAN DALAM MENGAMANKAN PILKADA SERENTAK 2024 DI KABUPATEN FAKFAK - Qasyim Hamidi, Muhammad; Murary, Weron; R. Morintoh, Raymond (Ensiklopedia of Journal, 2025)
The purpose of this research is to implement the simultaneous regional elections in 2024 in accordance with Law Number 10 of 2016 concerning the election of Governors, Regents, and Mayors, the election of regional heads has a strategic meaning for a democratic country. The police are a state tool tasked with maintaining public security and order, providing protection, and providing protection to the community, approaching the day of voting at the polling station, so the West Papua Regional Police has strengthened security in Fakfak Regency through 45 West Papua Police Operation Control Assistance Personnel to ensure the smooth implementation of the Regional Elections is a top priority in order to maintain stability and public order in the jurisdiction of the West Papua Police.This research is an empirical normative legal research or commonly known as empirical juridical, which is legal research that combines normative research methods and empirical research methods, legal research makes the norm system as the center of its study, or the norm system in a simple sense, namely rules or rules. The source of data is divided into two, primary data is data made by the researcher for the specific purpose of solving the problem he is handling, while secondary data is data that has been collected for purposes other than solving the problem at hand, the analysis of data obtained from the results of the research is compiled systematically and then analyzed using qualitative analysis methods, from the results a conclusion will be drawn which is the answer to the The problems raised in this study.From the results of the research, it was found that the National Police as the front line of maintaining public security and order has a central role to ensure that the election process runs smoothly, safely and conducively, to anticipate various potential threats, the National Police has prepared a measurable strategy. One of the pillars of this strategy is the strengthening of security since the pre-election stage, where in the regional election stage that has been held, conflicts between candidate supporters, the spread of hoaxes and other potential security disturbances often arise. The limited number of personnel, equipment, logistics, and budget can hinder the effectiveness of securing the regional elections, capacity building, such as training, equipment procurement, and the use of advanced technology, is essential to overcome these limitations. Police officers face political pressure from various interested parties, which can affect their neutrality and professionalism. Potential social conflicts, threats of violence, election fraud, and technical disruptions are challenges in maintaining security during the Regional Elections, comprehensive and coordinated security, as well as community involvement in supervision, can help overcome. Keywords: Fakfak Regional Elections, Police Role, Security.